Risk Factors for Umbilical Cord Prolapse at the Time of Artificial Rupture of Membranes - Kawakita, Tetsuya; Huang, Chun-Chih; Landy, Helain J. (American Journal of Perinatology Reports, 2018)
Objective The aim of the study was to examine the association between cervical exam at the time of artificial rupture of membranes (AROM) and cord prolapse.Study Design We conducted a retrospective cohort study using the data from the Consortium on Safe Labor. We included women with cephalic presentation and singleton pregnancies at ≥ 23 weeks' gestation who underwent AROM during the course of labor. Multivariable logistic regression was used to calculate the adjusted odds ratio (aOR) with 95% confidence interval (95% CI), controlling for prespecified covariates.Results Of 57,204 women who underwent AROM, cord prolapse occurred in 113 (0.2%). Compared with dilation 6 to 10 cm + station ≥ 0 at the time of AROM, <6 cm + any station and 6–10 cm + station ≤ −3 were associated with increased risks of cord prolapse (<6 cm + station ≤ −3 [aOR, 2.29; 95% CI, 1.02–5.40]; <6 cm + station −2.5 to −0.5 [aOR, 2.34; 95% CI, 1.23–4.97]; <6 cm + station ≥ 0 [aOR, 3.31; 95% CI, 1.39–8.09]; and 6–10 cm + station ≤ −3 [aOR, 5.47; 95% CI, 1.35–17.48]).Conclusion Cervical dilation < 6 cm with any station and 6 to 10 cm with station ≤ −3 were associated with a higher risk of cord prolapse.
Keywords: artificial rupture of membranes; cervical dilation; cord prolapse; fetal station; risk factors